The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1987
DOI: 10.1159/000184341
|View full text |Cite
|
Sign up to set email alerts
|

Magnesium, Calcium and PTH Relationships in Dialysis Patients after Magnesium Repletion

Abstract: Sixteen end-stage renal disease patients who received hemodialysis for 2.9 years with no magnesium in the dialysate were evaluated for serum calcium, magnesium and parathyroid hormone (PTH) status. Eleven of these patients became hypomagnesemic with subnormal total and ultrafiltrable serum Mg concentrations (low-Mg group). The five remaining patients had consistently normal serum Mg concentrations (normal-Mg group). All had normal total and ionized serum Ca. However, the total and ionized serum Ca levels in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

1989
1989
2017
2017

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 13 publications
1
14
0
Order By: Relevance
“…Kenny et al. (72) suggested that a low Mg dialysate might be expected to have a suppressive effect on parathyroid gland function; however, most studies failed to confirm this hypothesis. Several trials on the successful use of Mg salts to control hyperphosphatemia and hypeparathyroidism (73–76) support the hypothesis that hypermagnesemia may have a suppressive effect on PTH secretion in dialysis patients (77,78).…”
Section: Magnesium Parathyroid Hormone and Bone Diseasementioning
confidence: 99%
“…Kenny et al. (72) suggested that a low Mg dialysate might be expected to have a suppressive effect on parathyroid gland function; however, most studies failed to confirm this hypothesis. Several trials on the successful use of Mg salts to control hyperphosphatemia and hypeparathyroidism (73–76) support the hypothesis that hypermagnesemia may have a suppressive effect on PTH secretion in dialysis patients (77,78).…”
Section: Magnesium Parathyroid Hormone and Bone Diseasementioning
confidence: 99%
“…Some studies [48,50] indicated that serum Mg level did not influence PTH in patients on regular HD. Other studies reported a highly significant inverse correlation between Mg and PTH in HD patients [46,47,49,51,52,[55][56][57]65] . Table 1 summarizes data from clinical trials addressing the effect of Mg on serum PTH level in HD patients.…”
Section: Mg In Hemodialysis Patientsmentioning
confidence: 99%
“…In patients on HD, there is rapid equilibration between dialysate Mg and the ultrafilterable (nonprotein bound) Mg fraction in the blood; dialysate Mg is thus a major determinant of serum levels . Magnesium‐free dialysate is associated with high rates of hypomagnesemia . Hypomagnesemia can also be induced with dialysate Mg concentrations as high as 0.5 mmol/L .…”
Section: Magnesium Homeostasis In Health and On Dialysismentioning
confidence: 99%